Performance and Environmental Impacts Review of Li-Fi and Wi-Fi Technologies - Christoforus Williem Deo Lumoindong; Andre Muslim; Burawi Mohamed Nasreddin; Mia Galina (President University, 2018)
Nowadays, internet connectivity is one of the staple things in human lifestyle, especially for those who live in cities. There are a lot of ways to connect to the internet, and one of them is using Wi-Fi (Wireless Fidelity) connection. Wi-Fi connection is seen as the most reliable connection, until Li-Fi (Light Fidelity) technology is coined in 2011. Li-Fi uses visible light as data transfer medium instead of radio frequency (RF) signal used by Wi-Fi. Theoretically, Li-Fi is able to reach hundred times of Wi-Fi connection speed due to their use of light as data transfer medium. Li-Fi is also expected as a solution to environmental problems caused by Wi-Fi. The RF signal used by Wi-Fi can cause some environmental problems such as growth inhibition and diseases to organisms including humans. The visible light used by Li-Fi is expected to cause minimal effects to the environment, as Li-Fi uses common LED light bulbs which are used as home lighting apparatus. Li-Fi is commonly seen as a ‘greener’ technology compared to Wi-Fi. In this review, the performance and environmental impacts of both Wi-Fi and Li-Fi are analysed to determine whether Li-Fi is really capable to be a ‘greener’ replacement to Wi-Fi technology